2011
DOI: 10.1017/cbo9780511762574
|View full text |Cite
|
Sign up to set email alerts
|

Collective Killings in Rural China during the Cultural Revolution

Abstract: The violence of Mao's China is well known, but its extreme form is not. In 1967 and 1968, during the Cultural Revolution, collective killings were widespread in rural China in the form of public execution. Victims included women, children, and the elderly. This book is the first to systematically document and analyze these atrocities, drawing data from local archives, government documents, and interviews with survivors in two southern provinces. This book extracts from the Chinese case lessons that challenge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(25 citation statements)
references
References 167 publications
0
25
0
Order By: Relevance
“…Social scientific research on genocide has much to gain from increased attention to developments in the field of collective action, and a collective action approach to genocide would consider it one form of contentious politics among others, analyzable within the existing framework of social movement theory. Su (2011) who develops a community model to explain collective killing in rural China during the cultural revolu i -tion, perhaps comes closest to analyzing genocide from a collective action perspective. His analysis of violence in Guangxi and Guangdong draws on concepts of collective action such as identity formation, resource mobilization, political opportunity structures, and framing.…”
Section: Resultsmentioning
confidence: 99%
“…Social scientific research on genocide has much to gain from increased attention to developments in the field of collective action, and a collective action approach to genocide would consider it one form of contentious politics among others, analyzable within the existing framework of social movement theory. Su (2011) who develops a community model to explain collective killing in rural China during the cultural revolu i -tion, perhaps comes closest to analyzing genocide from a collective action perspective. His analysis of violence in Guangxi and Guangdong draws on concepts of collective action such as identity formation, resource mobilization, political opportunity structures, and framing.…”
Section: Resultsmentioning
confidence: 99%
“…Social scientific research on genocide has much to gain from increased attention to developments in the field of collective action, and a collective action approach to genocide would consider it one form of contentious politics among others, analyzable within the existing framework of social movement theory. Su (2011), who develops a community model to explain collective killing in rural China during the cultural revolution, perhaps comes closest to analyzing genocide from a collective action perspective. His analysis of violence in Guangxi and Guangdong draws on concepts of collective action such as identity formation, resource mobilization, political opportunity structures, and framing.…”
Section: Resultsmentioning
confidence: 99%
“…31), and edited volumes such as Bosi et al () “Dynamics of Politics Violence” likewise emphasize connections between contention and violence. Similarly, scholars in the United States and elsewhere increasingly devote their attention to the study of far‐right and left‐wing extremist activism (Dobratz and Waldner ; Klandermans and Mayer ; McVeigh ), militant nationalism (Demetriou ; Maney ), terrorism (Beck ; della Porta ; Goodwin ; Oberschall ), guerrilla warfare (Viterna , ), counter‐insurgency (Blocq ), armed activism (Bosi ; Bosi and della Porta ), violence as an escalation of action repertoires in response to state repression (della Porta ; Koopmans ), collective killings (Su ), and political violence against civilians (Maney et al ). This is a significant amount of research, indeed.…”
Section: Recent Divergencementioning
confidence: 99%
“…Other factors may have influenced the state's ability to implement this violence across Rwanda. Although the literature on civil war has found that distance from the center of a country provides opportunity for anti‐state insurgency (Cederman, Buhaug, and Rød, ; Fearon and Laitin, ; Murshed and Gates, ) and other unsanctioned violence (Su, ), proximity to the center of a country during state‐led violence may lead to increased violence. In this case, the genocide in Rwanda was centrally organized (Des Forges, ).…”
Section: Subnational Variation In Violencementioning
confidence: 99%